PERAN GURU DALAM MENGINTEGRASIKAN SIKAP PEDULI LINGKUNGAN MELALUI PEMBELAJARAN IPAS DI SDN KALIDERES 06 PAGI KELAS V - Safrudin, Barry; Dwi Hartanti, Saktian; Amaliya, Aam; Dorahman, Boy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of instilling environmental care attitudes from an early age through instruction in elementary schools, particularly in the Natural and Social Sciences (IPAS) subject. Teachers play a strategic role in integrating environmental care values into the learning process so that students not only acquire knowledge but also develop character that values the environment. This study aims to describe the teacher's role in integrating environmental care attitudes through IPAS instruction among fifth-grade students at SDN Kalideres 06 Pagi. A descriptive qualitative approach was employed, involving a fifth-grade teacher and six fifth-grade students as subjects. Data were collected through observation, interviews, and documentation, validated through source and technique triangulation, and analyzed through data reduction, data display, and conclusion drawing. The results indicate that the teacher optimally fulfilled the roles of motivator, facilitator, corrector, demonstrator, and inspirator in integrating environmental care attitudes through IPAS instruction. These roles positively influenced the formation of students' environmental care attitudes, such as maintaining cleanliness, disposing of waste properly, sorting waste, and keeping waterways and the school environment clean.